Improved stability of nano-sized La0.6Sr0.4Co0.2Fe0.8O3-δ-Ce0.8Sm0.2O1.9 composite cathodes by substituting Sr2+ with Ca2+. (10th July 2020) - Xu, Hongmei; Sun, Kaili; Cheng, Juanjuan; Wan, Feng; Chu, Aimin
Abstract: The nano-sized composite cathodes prepared by infiltrating La0.6 Sr0. 4 Co0.2 Fe0.8 O3-δ (LSCF) or La0.6 Ca0.4 Co0.2 Fe0.8 O3-δ (LCCF) into the Ce0.8 Sm0.2 O1.9 (SDC) scaffolds exhibit different electro-catalytic activity and microstructure evolution. Compared with LSCF-SDC nano-sized composite cathode, the LCCF-SDC composite cathode shows the higher microstructure stability. There is no observable coarsening or sintering and no diffraction peaks of other impurity phase are detected for both LSCF and LCCF after being aged at 600 °C for 500 h, but the lattice distortion is less if La 3+ ions are substituted by Ca 2+ ions instead of by Sr 2+ in LaCo0.2 Fe0.8 O3-δ (LCFO) lattice. The oxygen vacancy concentration is also less in LCCF than in LSCF. The less lattice distortion and oxygen vacancy concentration prohibit the Ca 2+ ions segregation on the LCCF cathode surface because of less strain in the LCCF lattice and less electrostatic interactions between the negatively charge A-site dopants (Ca′La ) and the positively charged oxygen vacancies (Vo ·· ) on LCCF surface. The greater binding energy of Ca–O maybe also hinder the enrichment of Ca 2+ ions on the cathode surface. After being aged in air at 600 °C for 500 h, more Sr 2+ ions gather on the LSCF cathode surface to form a Sr-rich inert phase, which is detrimental to the oxygen reduction reaction on the cathode surface. Highlights: The La0.6 Ca0.4 C0.2 Fe0.8 O3-δ -SDC nano-sized cathode is prepared by infiltration. The Rp of La0.6 Ca0.4 C0.2 Fe0.8 O3-δ -SDC cathode is close to that of LSCF-SDC cathode. The La0.4 Ca0.6 C0.2 Fe0.8 O3-δ -SDC composite cathode shows the higher stability.